The Quality of Clinical Practice Guidelines and Consensuses on the Management of Primary Aldosteronism: A Critical Appraisal - Meng, Zhe; Zhou, Liang; Dai, Zhe; Xu, Chang; Qian, Guofeng; Peng, Mou; Zhu, Yuchun; Kwong, Joey S. W.; Wang, Xinghuan (Frontiers in Medicine, 2020)
Background: Several guidelines and expert consensuses have been developed for management of primary aldosteronism (PA). It is important to understand the detailed recommendations and quality of these guidelines to help physicians make informed and reliable decision. Methods: PubMed, Embase and three websites were searched for practice guidelines or consensuses of PA from inception to Jan-24, 2019. We summarized the major recommendations on the management of PA from these guidelines and consensuses. The Appraisal of Guidelines for Research and Evaluation (AGREE) II was used to assess quality of the included guidelines and consensuses. Results: We identified 3 clinical practice guidelines and 3 consensus statements. Most of the recommendations on the diagnosis and treatment of PA from these guidelines and consensuses were consistent. Some minor conflicts were recorded for patient’s screen and confirmation test. All included guideline documents have a good quality (score > 70%) on the scope and purpose (mean score: 81.02%) and clarity of presentation of the recommendations (mean score: 86.88%). However, the reporting for the stakeholder involvement (mean score: 54.32%) and applicability (mean score: 47.92%) were insufficient. There was an insufficient rigorousness in most of the guideline documents (mean score: 45.56%) on the development process. The Endocrine Society practice guideline 2016 ranked highest in quality (score: 81.13%). Conclusions: Existing guideline documents provided valuable recommendations on the management of PA, but further efforts are needed to improve the methodological quality. The Endocrine Society practice guideline 2016 was recommended for use.